2016
DOI: 10.1038/srep18896
|View full text |Cite
|
Sign up to set email alerts
|

Sertoli cells have a functional NALP3 inflammasome that can modulate autophagy and cytokine production

Abstract: Sertoli cells, can function as non-professional tolerogenic antigen-presenting cells, and sustain the blood-testis barrier formed by their tight junctions. The NOD-like receptor family members and the NALP3 inflammasome play a key role in pro-inflammatory innate immunity signalling pathways. Limited data exist on NOD1 and NOD2 expression in human and mouse Sertoli cells. Currently, there is no data on inflammasome expression or function in Sertoli cells. We found that in primary pre-pubertal Sertoli cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 61 publications
2
28
0
Order By: Relevance
“…Interleukin 1 (IL-1) exists as two major agonist isotypes, IL-1α, and IL-1β, and these cytokines have a naturally antagonist named IL-1 receptor antagonist (IL-1ra). In rodent testis, IL-1α, and IL-1β are produced by Sertoli cells, interstitial macrophages and Leydig cells (111115). The production of IL-1α by human Sertoli and Leydig cells has also been demonstrated (116).…”
Section: Main Factors Involved In the Stimulation Of Sertoli Cell Promentioning
confidence: 99%
“…Interleukin 1 (IL-1) exists as two major agonist isotypes, IL-1α, and IL-1β, and these cytokines have a naturally antagonist named IL-1 receptor antagonist (IL-1ra). In rodent testis, IL-1α, and IL-1β are produced by Sertoli cells, interstitial macrophages and Leydig cells (111115). The production of IL-1α by human Sertoli and Leydig cells has also been demonstrated (116).…”
Section: Main Factors Involved In the Stimulation Of Sertoli Cell Promentioning
confidence: 99%
“…NLRP3 and ASC promote the cleavage of pro-caspase-1 and form an active complex, which triggers the cleavage of pro-IL-1b into mature IL-1b (9). In a murine model of UPEC orchitis, NLRP3, ASC, caspase-1, and IL-1b are clearly elevated in TM (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…They depend on enzymes (16) and cytokines (17) that participate in inflammatory process of male genitalia (14) . Group of researchers highlighted the importance of inflammasome protein NLRP3 as a "physiological low level of inflammation" for fertility (6).It had been suggested that low level of NLRP3 is essential for Sertoli cell production of low levels of IL1B to maintain IL1 alpha (18) but higher rate of inflammasome expression will results in higher level of inflammasome activation cytokines such as IL-1B and IL-18 (19) and served as a proinflammatory signals generating an inflammatory process in the testis such as leucocyte infiltration and cell death signaling and caspase 1 activation (20)(21)(22) .Also, it might activate ASC adaptor protein in both sperm cell and leucocytes in semen resulting in inflammatory cell death (23) . To date, the primary focus of inflammasome research has been anchored by NLRP3, which is a cytoplasmic protein that is primarily expressed in monocytes, macrophages, granulocytes, dendritic cells, epithelial cells and osteoblasts (24).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the primary focus of inflammasome research has been anchored by NLRP3, which is a cytoplasmic protein that is primarily expressed in monocytes, macrophages, granulocytes, dendritic cells, epithelial cells and osteoblasts (24). NLRP3 expression in myeloid cells is highly inducible (25) and other epithelial and Sertoli cells (6). So, the leukocyte counting is not always giving a true picture of inflammation, because of wide range of cells have the ability to respond and considered as a source of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation